The Training Characteristics of World-Class Male Long-Distance Cross-Country Skiers - Torvik, Per-Øyvind; Solli, Guro Strøm; Sandbakk, Øyvind (Frontiers in Sports and Active Living, 2021)
Purpose: To investigate the training characteristics of world-class long-distance cross-country skiers. Methods: Twelve world-class male long-distance cross-country skiing specialists reported training from their best season, through a questionnaire and follow-up interviews. Training data were systemized by training form (endurance, strength, and speed), intensity [low- (LIT), moderate- (MIT), and high-intensity training (HIT)], and exercise mode, followed by a division into different periodization phases. Specific sessions utilized in the various periodization phases were also analyzed. Results: The annual training volume was 861 ± 90 h, consisting of 795 ± 88 h (92%) of endurance training, 53 ± 17 h (6%) of strength training, and 13 ± 14 h (2%) of speed training. A pyramidal (asymptotic) endurance training distribution was employed (i.e., 88.7% LIT, 6.4% MIT, and 4.8% HIT). Out of this, 50–60% of the endurance training was performed with double poling (DP), typically in the form of a daily 3- to 5-h session. A relatively evenly distributed week-to-week periodization of training load was commonly used in the general preparation period, whereas skiers varied between high-load training weeks and competition weeks, with half the training volume and a reduced amount of DP during the competition period. Conclusions: To match the specific demands of long-distance cross-country skiing, specialized long-distance skiers perform relatively long but few training sessions and use a pyramidal intensity distribution pattern and a large amount of training spent using the DP technique.